Percutaneous treatment of stenosed major aortopulmonary collaterals with balloon dilatation and stenting: what can be achieved?. Issue 1 (1st January 1998) - Brown, S C; Eyskens, B; Mertens, L; Dumoulin, M; Gewillig, M
Abstract : Background: The natural history of major aortopulmonary collateral arteries (MAPCAs) in patients with pulmonary atresia and ventricular septal defect (PA-VSD) is frequently complicated by progressive stenosis, leading to pulmonary hypoperfusion and debilitating hypoxaemia. Objective: To evaluate balloon dilatation and stenting for relief of stenoses and improvement of pulmonary flow in patients with PA-VSD. Design: Retrospective analysis of all patients where dilatation of MAPCA stenoses was attempted. Patients: Twelve patients with stenotic MAPCAs. Interventions: Dilatation was attempted in 25 stenoses. Vessels were stented if elastic recoil was noticed (n = 3), in the presence of long segment stenosis (n = 4) or marked tortuosity (n = 1). Main outcome measures: Diameter of stenoses before and after dilatation as well as arterial oxygen saturation data. Patients proceeding to surgical therapy. Results: Two stenosed MAPCAs could not be crossed by a catheter. Four lesions were non-dilatable despite the use of high inflation pressures (18 atm). Six stenoses could be completely dilatated using angioplasty only; in five, only partial dilatation was obtained; eight stenoses needed stenting. In the group with partial expansion the mean (SD) diameter increased from 1.7 (0.8) to 3.5 (1.7) mm (p < 0.05); where full dilatation was achieved it increased from 2.1 (0.8) to 4.8 (1.9) mm (p < 0.05); and in the stented group it increased from 2.3 (0.9) to 5.0 (2.5) mm (p < 0.01). Percutaneous arterial oxygen saturation increased from 75(8)% to 82(8)% (p < 0.001). No complications were experienced during the procedures. Repeat dilatation was attempted in six stenoses, but only two procedures were successful. There were two episodes of vasospasm and in one an aneurysm had developed after redilatation. Two patients proceeded to outflow plasty and two subsequently had a unifocalisation procedure. Conclusions: Pulmonary blood flow can be improved using balloon angioplasty or stents in patients with stenotic MAPCA; however, 17% of the lesions were not dilatable. Procedures are generally safe, but carry a small risk of vasospasm, dissection, occlusion or aneurysm formation.